Dynamics of Intestinal Inflammatory Cytokines and Tight Junction Proteins of Turbot (Scophthalmus maximus L.) During the Development and Recovery of Enteritis Induced by Dietary β-Conglycinin - Zheng, Jing; Yang, Pei; Dai, Jihong; Yu, Guijuan; Ou, Weihao; Xu, Weiqi; Mai, Kangsen; Zhang, Yanjiao (Frontiers in Marine Science, 2020)
This study was conducted to investigate the dynamics characterization of enteritis of juvenile turbot (Scophthalmus maximus L.), during the development of enteritis induced by dietary β-conglycinin and the recovery by fish meal. Two isonitrogenous and isolipidic experimental diets were formulated, fish meal (FM) diet and fish meal supplemented with 8% β-conglycinin (7S) diet. The feeding trial consist of three groups, (1) turbot fed FM and 7S diet for ten weeks respectively, (2) turbot fed 7S diet for three weeks and then fed FM diet for another seven weeks (7S&FM). The distal intestines and serum of turbot in 7S&FM group were sampled at the 0 day, 3rd day, 1st week, 2nd week, 3rd week, 6th week and 10th week. After ten weeks feeding, the growth performance and feed utilization of turbot in FM and 7S&FM group were significantly higher than that of turbot in 7S group. According to the observation of intestine histology, the typical symptoms of enteritis were observed in the third week and then mitigated by fish meal gradually until the tenth week. The activities of DAO and content of D-lactate in serum showed the similar trend in ten weeks. The gene expression of pro-inflammatory cytokines IL-1β, IL-8, IL-22 and IFN-γ was significantly increased by 7S in the first three weeks and then significantly decreased by FM since the sixth week, as well as the expression of NF-κB. The opposite trend of gene expression was observed in anti-inflammatory cytokine TGF-β. The gene expression of tight junction proteins claudin-3, claudin-4, claudin-like, occludin and ZO-1 was significantly decreased during the first three weeks and then the gene expression of claudin-4 and occludin was significantly increased by dietary fish meal since the sixth week. Meanwhile, the gene expression of MLCK increased significantly during the first three weeks and then significantly declined at the tenth week. Collectively, dietary 8% β-conglycinin could induce the serious enteritis of turbot in three weeks and the mitigation progress could be observed when turbot fed fish meal diet. The intestinal inflammatory cytokines and tight junction proteins showed different responses during the development and recovery of enteritis.